Characterization and environmental performance evaluation of locally manufactured P-32 and commercial activated carbons on the Ghanaian market - Isaac K. Tetteh; Solomon Nandomah; Janet A. Boadu; Amos Nortey; Esther B. Dwemoh; Antonia Y. Tetteh (Sustainable Chemistry for the Environment)
This study characterizes and evaluates the environmental performance of P-32 Activated Carbon (AC), and commercial AC (CAC). Physicochemical properties ─ bulk density, porosity, moisture, ash content, pH, electrical conductivity (EC), and adsorptive properties ─ methylene blue number (MBN) and iodine number (IN), were investigated using standard methods based on particle size (powdered: ≤ 53 µm; granular: 1.0 – 2.8 mm). Intercorrelation matrices, descriptive statistics, and Analysis of Variance (ANOVA) were used for properties intercomparison. Multiple linear regression analysis (MLRA) was performed with candidate predictors from the intercorrelation matrices to predict MB and I2 adsorption. Environmental performance was evaluated using paired sample t-test by reviewing the adsorption performance of P-32 Powdered AC (PAC) and commercial PAC (CPAC) targeting seven potentially toxic elements (PTEs) ─ iron (Fe), cadmium (Cd), copper (Cu), chromium (Cr), zinc (Zn), arsenic (As), and manganese (Mn) in mine-impacted surface water. Except for bulk density and ash content, P-32 AC exhibited lower physicochemical properties and MB/IN adsorption than CAC. Also, CAC demonstrated stronger relationships among properties than P-32 AC. Particle size, bulk density, and moisture content significantly predicted CAC’s IN adsorption, whereas particle size and porosity predicted P-32 AC’s IN. Particle size significantly predicted CAC’s MBN, while all the predictors favored P-32 AC’s MBN prediction. Percent removal (% R) of the PTEs by CPAC (P-32 PAC) ranged from 44.44 ─96.50 % (62.96 ─ 98.25 %) across incremental carbon masses (5.00─25.00 g)/L effluent. P-32 PAC significantly outperformed CPAC in the remediation (p < 0.05), revealing discrepancies between laboratory-based adsorption experiments and real-world environmental performance.